Analisis SWOT Terhadap Strategi Pemasaran (Studi Kasus Rumah Sakit Swasta AA Karawang) - Taslim, Ricky; Nurhaliza, Zalsa; Pangestika, Zalma Niendya (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2024)
The research aims to identify every factor that can affect marketing strategies based on SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) and assist Karawang Private Hospital in deciding which marketing strategy is right to apply. The case population of this study consisted of employees of private hospitals. Sampling using purposive sampling. The resources used come from information providers, locations, and events. The data collection techniques used were interviews in the form of questions and questionnaire questionnaires. Verification of the validity of the data is done by source triangulation and method triangulation. The data analysis techniques used are IFAS (Internal Factor Analysis Summary) quadrant matrix and EFAS (Internal Factor Analysis Summary) matrix. The results of the study concluded that the marketing strategy of Karawang Private Hospital was determined based on SWOT analysis. With the results of data analysis, the highest strength factor value of 2.511, the highest weakness value of 1.156, the highest chance value of 1.527, and the highest threat value of 1.691 were obtained. The total score of the IFAS matrix is 1.356 and the EFAS matrix is (-) 0.164. The recommended marketing strategy is a diversification strategy.